Utilizing Artificial Intelligence in Language Learning: What About Engineering Students"™ Perception? - Persulessy, Sylvia Irene; Nikijuluw, Reynold P. J. Vigeleyn; Jakob, Juvrianto Chrissunday (Journal of English Education Program, 2024)
Presented as a technological innovation set to usher in significant changes globally, artificial intelligence (AI) enters various segments of life, especially in the field of education. Civil engineering students, as part of their learning journey, try to apply it in class, especially in aspects of engineering English vocabulary. In the current study, students used the English Language Speech Assistant (ELSA) application. The research method used was descriptive research, where the research subjects were taken from 1 class of 29 students. In this study the questionnaires were used as instruments to collect research data. Based on the results of survey analysis and data collected, it was revealed that students had very good and positive perceptions of using the ELSA application. Students exhibit great joy and enthusiasm in learning engineering English vocabulary using the ELSA application. In addition to offering an effective means of pronouncing vocabulary words, this application's feedback also serves as a motivational factor to learn engineering English vocabulary. Thus, the student's positive perspective on this application of AI can be an indicator of the success of students' language learning in the future.